PENGEMBANGAN E-MODUL KIMIA BERBASIS INTRODUCTION, CONNECT, APPLY, REFLECT, EXTEND (ICARE) PADA MATERI REAKSI REDOKS - Nengsih, Ersa Agusti; Amir, Hermansyah; Handayani, Dewi (ALOTROP, 2023)
This study is a research and development of ICARE-based chemistry e-modules that aims to determine the feasibility of e-modules, student responses, and improvement of student learning outcomes. The development model used is analysis, design, development, implementation, evaluation (ADDIE). The research was conducted at SMA Negeri 2 Seluma from January to August 2022. The subjects of this study were X IPA 2 and X IPA 3 students in the 2022/2023 school year who were selected based on simple random sampling techniques with a population of 3 classes, which were then tested for normality and homogeneity so that normal and homogeneous classes were obtained, namely X IPA 2 class for small group tests and X IPA 3 for large group tests. The instruments in this study were interview sheets, validation sheets, student response questionnaires, and tests. From the results obtained (1) ICARE-based chemistry e-modules were declared very feasible by media and material experts with a percentage of 98.88% media aspects and 91.25% material aspects, (2) Student responses to ICARE-based chemistry e-modules were in the very good category with an average percentage of 90.23%, and (3) After using ICARE-based chemistry e-modules on redox reaction material, there has been an increase in student learning outcomes as measured by an average N-gain score of 0.69 on moderate criteria. The results of the development of ICARE-based chemistry e-modules are very feasible to use in the learning process and proven to improve student learning outcomes. Keywords: e-module, development, ICARE, learning outcomes